2023
DOI: 10.3389/fenrg.2023.1120635
|View full text |Cite
|
Sign up to set email alerts
|

Study on the mechanism of improved oil recovery by nitrogen foam flooding in bottom water reservoirs

Abstract: There are abundant bottom water reservoirs in China. Unlike conventional oil reservoirs, bottom water reservoirs have various problems, such as early water breakthrough, short water-free oil recovery period, and rapid water cut increase. For example, during water flooding, the injected water easily breaks into the bottom water and does not effectively displace the upper crude oil. The recovery rate is generally low. Based on this phenomenon, an experimental study of nitrogen foam flooding in bottom water reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Sandstone reservoirs with bottom water drive are important parts of unconventional petroleum resources, which are characterized by early water breakthrough, short water-free oil recovery period, rapid water cut increase, and strong heterogeneity. With large scale and high abundance, bottom water reservoirs are strictly controlled by structure, stratum, and other conventional traps. Since natural interbeds between sandstone reservoirs and the bottom aquifer are usually weak or absent, water can easily intrude the production wells and the oil/water interface moves toward the wellbore. , Once water breakthrough occurs, the water cut increases significantly, which inhibits the flow of oil, and a large amount of residual oil remains in the middle and upper part of the reservoir, reducing production efficiency. Therefore, the exploitation of sandstone reservoirs with bottom water drive suffers from the bottom water coning and huge production cost issues. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sandstone reservoirs with bottom water drive are important parts of unconventional petroleum resources, which are characterized by early water breakthrough, short water-free oil recovery period, rapid water cut increase, and strong heterogeneity. With large scale and high abundance, bottom water reservoirs are strictly controlled by structure, stratum, and other conventional traps. Since natural interbeds between sandstone reservoirs and the bottom aquifer are usually weak or absent, water can easily intrude the production wells and the oil/water interface moves toward the wellbore. , Once water breakthrough occurs, the water cut increases significantly, which inhibits the flow of oil, and a large amount of residual oil remains in the middle and upper part of the reservoir, reducing production efficiency. Therefore, the exploitation of sandstone reservoirs with bottom water drive suffers from the bottom water coning and huge production cost issues. …”
Section: Introductionmentioning
confidence: 99%
“…In a bottom water drive reservoir, the low-permeability interbeds can prevent the injection water from flooding below the interbed where remaining oil can accumulate or decrease the flooding efficiency of the oil sheet above the interbeds due to their isolation effect. The distribution of interbeds’ feature can curb the occurrence of coning water effectively, which has a great influence on bottom water drive reservoir. , Therefore, it is of great scientific and engineering significance to systematically study the water flooding characteristics in the bottom water–oil reservoir containing interbeds. Wu et al investigated the mechanism of improved oil recovery by nitrogen foam flooding in bottom water reservoirs and revealed that the seepage resistance of foam in the water layer is much greater than that in the oil layer, effectively increasing the displacement strength of the oil layer. Liu et al used oil-soluble resin as selective water shut-off agent in artificial barriers and confirmed its important role in water control in low-permeability hydrocarbon reservoirs with bottom aquifers.…”
Section: Introductionmentioning
confidence: 99%